Teaching Domestic Violence in the New Millennium: Intersectionality as a Framework for Social Change. (October 2016) - McQueeney, Krista
This article describes an intersectional approach to teaching about domestic violence (DV), which aims to empower students as critical thinkers and agents of change by merging theory, service learning, self-reflection, and activism. Three intersectional strategies and techniques for teaching about DV are discussed: promoting difference-consciousness, complicating gender-only power frameworks, and organizing for change. The author argues that to empower future generations to end violence, educators should put intersectionality into action through their use of scholarship, teaching methods, and pedagogical authority. Finally, the benefits and challenges of intersectional pedagogy for social justice education are considered.